2019
DOI: 10.3389/fimmu.2019.00955
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Naïve T Cells Requires the Expression of Let-7 miRNAs

Abstract: Maintaining the diversity and constant numbers of naïve T cells throughout the organism's lifetime is necessary for efficient immune responses. Naïve T cell homeostasis, which consists of prolonged survival, occasional proliferation and enforcement of quiescence, is tightly regulated by multiple signaling pathways which are in turn controlled by various transcription factors. However, full understanding of the molecular mechanisms underlying the maintenance of the peripheral T cell pool has not been achieved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
(71 reference statements)
2
11
0
Order By: Relevance
“…Our most striking finding is that let-7 miRNAs keep pathogenic CD4 + T cells from infiltrating the CNS. This effect was not due to a detrimental impact of let-7 miRNAs on the survival of activated CD4 + T cells, as maintenance of high let-7 miRNA expression improved the survival rate of activated CD4 + T cells, while let-7 deficiency caused an increase in cell death, which is consistent with our recently published observations in both naïve CD4 + and CD8 + T cells that let-7 miRNAs promote homeostatic survival through IL-7-independent stabilization of Bcl2 expression (29).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our most striking finding is that let-7 miRNAs keep pathogenic CD4 + T cells from infiltrating the CNS. This effect was not due to a detrimental impact of let-7 miRNAs on the survival of activated CD4 + T cells, as maintenance of high let-7 miRNA expression improved the survival rate of activated CD4 + T cells, while let-7 deficiency caused an increase in cell death, which is consistent with our recently published observations in both naïve CD4 + and CD8 + T cells that let-7 miRNAs promote homeostatic survival through IL-7-independent stabilization of Bcl2 expression (29).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Let-7Tg cells exhibited better survival than their WT counterparts, while the recovery of Lin28Tg lymphocytes was significantly lower ( Figure 3A). In fact, these results are in agreement with our recently published findings in naïve CD4 and CD8 T cells (29), suggesting that let-7 expression also supports the survival of activated CD4 + T cells. Thus, the reduced numbers of CNS-infiltrated Let-7Tg CD4 + T cells recovered during EAE cannot be explained by increased cell death.…”
Section: Let-7 Promotes Survival But Restricts the Proliferation Of Asupporting
confidence: 93%
See 1 more Smart Citation
“…It has been shown that the let-7 family is expressed in T N cells, downregulated in T EFF cells and re-expressed in T M cells. 78,79 Downregulation of the let-7 family during the expansion phase is necessary for T cell proliferation and expansion. 80 Loss of let-7 increases T cell proliferation and effector function while it also promotes differentiation of terminal effector cells, mitochondria fission and AICD in T cells.…”
Section: Considerations When Selecting Mirnas For Expression In Car T...mentioning
confidence: 99%
“…80 Loss of let-7 increases T cell proliferation and effector function while it also promotes differentiation of terminal effector cells, mitochondria fission and AICD in T cells. 78,80 Many studies investigating the role of miRNAs in T cell function utilize murine models for infection settings. Whilst conserved miRNAs tend to have comparable targets and functions both in humans and mice, some miRNAs are divergent in both their function and targets.…”
Section: Considerations When Selecting Mirnas For Expression In Car T...mentioning
confidence: 99%